Faculty's and medical students' opinions towards the use of logbook at Department of Surgery, Bangkok Metropolitan Administration Medical College and Vajira Hospital. - Nataphon Santrakul (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2011